Materials qualification through the Nuclear Science User Facilities (NSUF): a case study on irradiated PM-HIP structural alloys - Wharry, Janelle P.; Guillen, Donna Post; Clement, Caleb D.; Bin Habib, Saquib; Jiang, Wen; Zhao, Yangyang; Lu, Yu; Wu, Yaqiao; Shiau, Ching-Heng; Frazer, David; Heidrich, Brenden J.; Knight, Collin; et al. (Frontiers in Nuclear Engineering, 2023)
This article presents neutron irradiation and post-irradiation examination (PIE) capabilities available to the nuclear materials research community through the US Department of Energy's Nuclear Science User Facilities (NSUF). The pressing need to deploy advanced nuclear reactors to combat climate change requires qualification of new fuels and material. Among advanced manufacturing processes, powder metallurgy with hot isostatic pressing (PM-HIP) is nearest to becoming qualified for nuclear applications.This article provides examples from a recent irradiation and PIE program on a series of structural alloys fabricated by PM-HIP to illustrate how NSUF capabilities can be used to generate qualification data. The neutron irradiation experiments are described, and a sampling of results from tensile testing, nanoindentation, transmission electron microscopy, and atom probe tomography are presented, showing the favorable performance of PM-HIP alloys compared to their cast or forged counterparts under irradiation.This article provides a perspective on leveraging NSUF for future nuclear fuels and materials testing and qualification.